Application of aqueous Ag:ZnInSe quantum dots to non-toxic sensitized solar cells1. Issue 57 (25th June 2015) - Wang, Zhao-Chong; Xu, Shu-Hong; Wang, Chun-lei; Zhu, Li; Bo, Fan; Lin, Xiao-Yan; Wang, Zhu-Yuan; Cui, Yi-Ping
<x xml:space="preserve">Abstract</x> A non-toxic, aqueous Ag:ZnInSe quantum dot-sensitized solar cell with an efficiency of 0.89% at 1 sun was fabricated.